Values, Ideologies, Attitudes, and Preferences for Relative Allocations to Park and Recreation Services. (18th August 2022) - Pitas, Nick A.; Mowen, Andrew; Taff, B. Derrick; Hickerson, Benjamin; Graefe, Alan
Abstract: Local park and recreation agencies rely heavily on tax-based allocations as a funding source. However, such allocations have recently been cut both overall and relative to other services, incentivizing exploration of alternative funding strategies. Privatization practices represent a potentially efficacious but controversial alternative funding approach. This study examines the relationship between attitudes toward privatization, and preferences for allocating tax-based funding to park and recreation services. The mediating role of other cognitive processes (values, value orientations, and ideology) is considered using a cognitive hierarchy approach. Results indicate that a more positive perception of privatization was related to the allocation of less tax funding to park and recreation services. A more self-transcendent value orientation was positively related to preferred allocations, while a more self-enhancement value orientation and a more conservative social ideology were negatively related to preferred allocations.